APPLICATION OF THE PRECAUTIONARY PRINCIPLE IN THE WTO - REACHES AND PERSPECTIVES - Divljak, Drago (Zbornik radova Pravnog fakulteta u Novom Sadu, 2022)
Abstract: The paper discusses the legal basis for the application of the precautionary principle in the WTO law, and determines the specifics of its application in relation to the basic concept of the precautionary principle. Special attention is paid to the analysis of the reach of this application in terms of opening up the optimal environmental protection. The paper also presents proposals for future normative solutions in this area with the aim of achieving an appropriate balance between the interests of international trade liberalization and environmental protection and accomplishing of the concept of sustainable development. With all the limitations related to the lack of adequate legal basis, but also the incompleteness and incoherence of the dispute resolution practice in the WTO, it can be concluded that the derived concept of application of the precautionary principle and its interpretation in the dispute resolution practice reduce the scope of its application in relation to the basic concept. Such a situation cannot meet in particular the needs of technological development, which inevitably leads to an increased risk in terms of impact on the environment, human health and flora and fauna. In such circumstances, when the importance of the application of this principle grows, it is necessary to find appropriate legal solutions that will ensure its optimal application. In this context, different models of action are possible, with all their limitations, the realization of which is quite questionable.
Keywords: Key words: precautionary principle, WTO, environmental protection, international trade, Agreement on Sanitary and Phyto-sanitary Measures